2016
DOI: 10.1002/jsfa.8090
|View full text |Cite
|
Sign up to set email alerts
|

Identification of black pine (Pinus nigraArn.) heartwood as a rich source of bioactive stilbenes by qNMR

Abstract: Pinus nigra heartwood is the richest source of pinosylvin and pinosylvin monomethyl ether identified to date and can be considered the best natural resource for production of bioactive extracts. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 45 publications
(81 reference statements)
0
25
0
5
Order By: Relevance
“…Reduced decay rate of dead wood decreases release of CO 2 back to the atmosphere. Concentrations of both resin acids ( Karppanen et al, 2007 ) and stilbenes ( Ioannidis et al, 2017 ) in heartwood of Pinus sp. can exceed 10% of dry weight and significantly reduce decay rate of dead wood by fungal rot ( Karppanen et al, 2007 ) and by woodborers ( Nerg et al, 2004 ).…”
Section: Psc Transmitted Ecosystem Feedbacks To Climate Changementioning
confidence: 99%
“…Reduced decay rate of dead wood decreases release of CO 2 back to the atmosphere. Concentrations of both resin acids ( Karppanen et al, 2007 ) and stilbenes ( Ioannidis et al, 2017 ) in heartwood of Pinus sp. can exceed 10% of dry weight and significantly reduce decay rate of dead wood by fungal rot ( Karppanen et al, 2007 ) and by woodborers ( Nerg et al, 2004 ).…”
Section: Psc Transmitted Ecosystem Feedbacks To Climate Changementioning
confidence: 99%
“…As it was previously shown in the cases of olive oil [43,44], beer [45], wine [33], and stilbenes from Pinus nigra heartwood [3], qNMR is the most appropriate method for quantitation. The developed methodology for the analysis of heartwood resin acids requires less than a minute to record the spectrum and perform the analytes quantitation, whereas using the previously reported 13 C-NMR methodology requires a considerably longer time, i.e., approximately two hours [40] or even more [46].…”
Section: Discussionmentioning
confidence: 99%
“…Venäläinen et al [48] also reported high variation among trees in the resin acid concentrations of Pinus sylvestris . Heartwood resin acid contents present provenance variation as well (Table 5) because of the heterogeneity among populations [3]. In general, the southeastern provenance of Parnonas, grown at the most xerothermic environment [49] and subjected to the strongest winds [50], showed higher values of total resin acids, i.e., for neoabietic acid, palustric acid, and sandaracopimaric acid, while the southwestern of Taigetos had the lowest concentrations of all except for dehydroabietic and levopimaric acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations